If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14k + 2(5k + -6) = -3k + -39 Reorder the terms: 14k + 2(-6 + 5k) = -3k + -39 14k + (-6 * 2 + 5k * 2) = -3k + -39 14k + (-12 + 10k) = -3k + -39 Reorder the terms: -12 + 14k + 10k = -3k + -39 Combine like terms: 14k + 10k = 24k -12 + 24k = -3k + -39 Reorder the terms: -12 + 24k = -39 + -3k Solving -12 + 24k = -39 + -3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '3k' to each side of the equation. -12 + 24k + 3k = -39 + -3k + 3k Combine like terms: 24k + 3k = 27k -12 + 27k = -39 + -3k + 3k Combine like terms: -3k + 3k = 0 -12 + 27k = -39 + 0 -12 + 27k = -39 Add '12' to each side of the equation. -12 + 12 + 27k = -39 + 12 Combine like terms: -12 + 12 = 0 0 + 27k = -39 + 12 27k = -39 + 12 Combine like terms: -39 + 12 = -27 27k = -27 Divide each side by '27'. k = -1 Simplifying k = -1
| -5x+2(1-7x)= | | -3(2s-2)-6=-2(6s+4)-3 | | 5x=100x | | (xy)dx+(2x^2+3y^2-20)dy=0 | | 5z=1.1+5.9 | | 8x-3x-102=-8x+39 | | 4x-4-3y+0=0 | | 5x-2x+3=3x-1+24 | | -7(4x+7)=-28x-49 | | x-2*((-x)-2)=5 | | 6b+7=8b-13 | | 10x+11=11x+1 | | 3z+3=8z-14 | | x^2+y^2-2x-16y+65=81 | | 88+.84x=x | | 5(6r-1)+5r= | | 5(-4n-3)=-55 | | 5x-2x=3x-2 | | 10x-2x-60=-10x+36 | | y=3ln(2x-3)+x^2 | | 12u^2-13u+3=0 | | x-2*(-x-2)=5 | | x-2*(-x+2)=5 | | 4p+6(p+3)= | | 39.89=8g+3.97 | | (-x)-2*(3x+1)=(-x)+(-8) | | 2e=4c-16 | | 22.11=4g+3.51 | | 36.40=7g+3.71 | | 5x+-y=17 | | 62x+3=64x-1 | | -3+-6(4x+6)=-111 |